The Effect of Digital Marketing on Increasing MSME Profits: Case Study: Ulubelu District - Pratama, Nando Rizky Arnando; Setiawan, Rahmat; Sanjaya, Vicky F (Bina Bangsa International Journal of Business and Management, 2022)
This study aims to examine the effect of digital marketing on increasing MSME profits. The method used in this study using a questionnaire. The sample used in this study amounted to 35 respondents. The statistical test was carried out using PLS-based structural equalization modeling. the validity test uses a loading factor, while the reliability test uses Cronbach's alpha value, composite reliability and average variance extracted (AVE). All proposed hypotheses are supported and significant. The conclusion of this study is the effect of digital marketing on increasing MSME profits